1991
DOI: 10.1091/mbc.2.1.41
|View full text |Cite
|
Sign up to set email alerts
|

Internalization pathway of C3b receptors in human neutrophils and its transmodulation by chemoattractant receptors stimulation.

Abstract: On the surface of phagocytes, C3b receptors (CR1) bind C3b-coated particles and promote their ingestion after activation by appropriate stimuli such as lymphokines or the chemoattractant formyl methionyl leucyl phenylalanine (fMLP) and fibronectin. The aims of the present study were 1) to define at the electron microscopic level the nature of the process responsible for CR1 internalization and 2) to dissect the mechanism by which a physiological activator (fMLP) stimulates this process. CR1 was visualized eith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 41 publications
0
33
0
Order By: Relevance
“…After two washes in 4°C phosphate-buffered saline, cells were warmed and kept 5 or 20 min in a 37°C water bath in the presence or in the absence of 2 g/ml Escherichia coli K12 LCD25 LPS (List Biological Laboratories Inc., Campbell, CA)/10% fetal bovine serum. Cells were then fixed for 30 min at 20°C with 2.5% glutaraldehyde diluted in pH 7.4 phosphate buffer, dehydrated, and processed for electron microscopy as described elsewhere (30). Thin sections were examined in a Philips electron microscope 301, and gold particles were quantitatively analyzed.…”
Section: Methodsmentioning
confidence: 99%
“…After two washes in 4°C phosphate-buffered saline, cells were warmed and kept 5 or 20 min in a 37°C water bath in the presence or in the absence of 2 g/ml Escherichia coli K12 LCD25 LPS (List Biological Laboratories Inc., Campbell, CA)/10% fetal bovine serum. Cells were then fixed for 30 min at 20°C with 2.5% glutaraldehyde diluted in pH 7.4 phosphate buffer, dehydrated, and processed for electron microscopy as described elsewhere (30). Thin sections were examined in a Philips electron microscope 301, and gold particles were quantitatively analyzed.…”
Section: Methodsmentioning
confidence: 99%
“…Unbound secondary antibody was removed by washing twice with ice-cold PBS, and cells were warmed for 5 min at 37°C to allow endocytosis. Cells were finally fixed 30 min at room temperature with 2.5% glutaraldehyde in phosphate buffer, dehydrated, and processed for electron microscopy as described previously (Carpentier et al, 1991). Thin sections were examined in a Philips EM 300 (Philips), and gold particles were quantitatively analyzed on cells considered well preserved.…”
Section: Acid Wash Assaymentioning
confidence: 99%
“…Heterologous regulation (i.e., receptor cross-talk) occurs when one receptor generates a second messenger that regulates the internalization of another receptor. Examples for the latter include the increased internalization of type 1 complement receptor after stimulation of the Nformylmethionylleucylphenylalamine (f-MLP) receptor (presumably via protein kinase C; Carpentier et al, 1991) and cyclic AMP (cAMP) enhanced internalization of adherence-receptors in neurons (through an increase in the number of clathrin-coated pits; Hu et al, 1993). cAMP has also been implicated in the regulation of CD4 capping and endocytosis after receptor multimerization in human T lymphocytes (Kammer et al, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Neutrophils in peripheral blood may be activated or primed with regard to superoxide production, chemotaxis, and increased expression of surface molecules such as CD35 which mediates the binding and phagocytosis of C3b-coated particles and immune complexes [28]. The study of Smith et al [29] suggested that upregulation of CD11b expression may be associated with neutrophils degranulation.…”
Section: Introductionmentioning
confidence: 99%